Koli delicacies during Narali Purnima - Mumbai Archive Project Team (Jio Institute, 2024)
Sweets and Koli delicacies like narali karanji (half-moon-shaped fried pastry made from grated coconut and jaggery mixed with dry fruits) and nariyal ladoo (sweet balls made from grated coconut mixed with jaggery and dry fruits) are offered as naivedya (sacred food offerings made to deities or nature). The items are typically prepared from coconut. Some naivedya items are also offered to the sea.